How does interactive virtual reality enhance learning outcomes via emotional experiences? A structural equation modeling approach - Yang, Hairu; Cai, Minghan; Diao, Yongfeng; Liu, Rui; Liu, Ling; Xiang, Qianchen (Frontiers in Psychology, 2023)
Introduction Interest in interactive virtual reality (IVR) is increasing due to its potential for embodied learning and group-led teaching. However, few studies have investigated the internal mechanism by which IVR technology features and learning experiences affect learning outcomes in terms of psychological and emotional value. Based on media technology models and the control value theory of achievement emotions (CVTAE), this study uses structural equation modeling (SEM) to investigate the correlations among the internal elements of IVR technology features, learning experiences, and learning outcomes. It also emphasizes the role played by emotional experience in this context. Methods The sample referenced by this study consisted of 480 college students (193 males) who were simultaneously engaged in guided inquiry and learning in an IVR-based COVID-19 pandemic science museum in groups of 10. Results The findings suggest that presence and perceived enjoyment have a key mediating effect on the relationship between virtual reality (VR) features and perceived learning outcomes in an IVR-based learning simulation. In addition, the results indicate that presence is more strongly correlated with perceived learning effects, while enjoyment is more strongly correlated with learning satisfaction. Discussion These findings provide intellectual support and theoretical backing for VR-based instructional design and environmental development. Moreover, this study has practical value with regard to the future large-scale application of IVR to experiential teaching, group-led teaching, and the promotion of the digital transformation and intelligence upgrading in education.